THE EFFICACY OF NITROXYNIL AGAINST MATURE AND IMMATURE FASCIOLA GIGANTICA IN EXPERIMENTALLY INFECTED SHEEP - A. Ali, S.; A. AL-Zahery, N. (The Iraqi Journal of Veterinary Medicine, 1988)
The anthelmintic efficacy of nitroxynil was tested in three groups (A, B and C) of artificially infected sheep with Fasciola gigantica. Bach animal was given six metacercariae/kg body weight. All animals were weighed weekly. Two groups of animals (A and B) were treated with 8 single dose of nitroxynil given subcutaneously. Gre A was treated at a dose rate of 15 mg/kg b.w. 8 weeks post infection, while group B drenched at a dose rate of 10 mg/kg b.w. 19 weeks post infection. During the study, it was observed that the average prepatent period of infected animals was 114 days. The results of the experiment were assessed by faecal egg count and autopsy examinations. All groups of animals were slaughtered at 21 weeks post infection. The fluke burden in group A was ranging from 2-7 worms in 5 animals out of 6 animals, whilst from group B no flukes recovered. Doses of 10 and 15 mg/kg proved 100 and 89.9% effective respectively, against mature and immature F. gigantica.